Biomarker of early neurological deterioration in minor stroke and proximal large vessel occlusion: A pilot study - Wang, Zhiqiang; Wang, Shuai; Li, Yuxia; Wang, Rongyu; Jiang, Lianyan; Zheng, Bo; Zhang, Yaodan; Wang, Qingsong; Wang, Jian (Frontiers in Neurology, 2022)
Background: Plasma neurofilaments light chain (pNFL) represents one of the scaffolding proteins of central nervous system axonal injury. The aim of this study was to evaluate pNFL as a predictive biomarker for early neurological deterioration (END) in medically managed patients with large vessel occlusion (LVO) and mild presentation(NIHSS<6). Methods: This retrospective study was developed from a prospectively collected stroke database, which was conducted at a large academic comprehensive stroke center in western China. Patients who first presented with acute ischemic stroke (AIS) within 24 hours of symptom onset were continuously included. Stroke severity was analyzed at admission using the NIHSS score. The pNFL drawn on admission was analyzed with a novel ultrasensitive single-molecule array. Results: Thirty-nine consecutive patients were included analysis, and 19 (48.72%) patients experienced END. Patients who experienced END had significant higher pNFL levels (mean, 65.20 versus 48.28 pg/mL; P<0.001), larger infarct volume (mean, 15.46 versus 9.56 mL; P<0.001). pNFL was valuable for the prediction of END (OR, 1.170; 95% CI, 1.049-1.306; P=0.005), even after adjusted for age and sex (OR, 1.178; 95% CI, 1.038-1.323; P=0.006), blood sampling time, baseline NIHSS, TOAST classification and infarct volume (OR, 1.168; 95% CI, 1.034-1.320; P=0.012). The area under the ROC curve was 85.0% (95% CI, 0.731-0.970; P<0.001). Sensitivity was 73.7%, specificity 80%. Conclusions: END in minor stroke with LVO were distinguishable from those without END following the determination of pNFL in the blood samples within 24 hours of onset. The pNFL is a promising biomarker of END in minor stroke with LVO. Clinical trial registration: ChiCTR1800020330.